Effectiveness of the Phenomenon-Based Approach in Enhancing Senior High School Students’ Mathematical Achievement and Problem-Solving Skills - Sabugal, Benjie T.; Apellido Jr, Engr. Eulogio (Bumi Publikasi Nusantara, 2025)
This study investigates the effectiveness of the Phenomenon-Based Approach (PBA) compared to the Traditional Approach (TA) in teaching mathematics to Senior High School students at Polonuling National High School, Philippines. Employing a quasi-experimental design, pre-tests and post-tests were administered to measure students' mathematical performance, particularly their problem-solving and critical thinking skills. The pretest scores showed no significant difference between the two groups, indicating comparable initial proficiency levels. However, post-test results revealed a statistically significant improvement in the PBA group, highlighting the approach's effectiveness in enhancing conceptual understanding and academic achievement. Statistical analysis confirmed the superior impact of PBA on student learning outcomes. The findings support the integration of PBA into classroom instruction to foster real-world application of mathematics and strengthen 21st-century competencies. The study recommends curriculum enhancement, teacher training, and interdisciplinary collaboration to facilitate effective implementation of the Phenomenon-Based Approach in the Philippine educational context.